Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fsurg.2022.783885
|View full text |Cite
|
Sign up to set email alerts
|

Using Local Anesthesia for Burr Hole Surgery of Chronic Subdural Hematoma Reduces Postoperative Complications, Length of Stay, and Hospitalization Cost: A Retrospective Cohort Study From a Single Center

Abstract: PurposeThe purpose of the current study was to compare the effects of local anesthesia (LA) and general anesthesia (GA) on the surgical process and postoperative recovery of patients with unilateral chronic subdural hematoma (CSDH).Patients and MethodsA retrospective cohort study was conducted on patients with unilateral CSDH who underwent burr hole surgery between the years 2013 and 2018. Patients who received local anesthesia were allocated to the LA group, and the patients who received general anesthesia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Hence, we noticed that GA length of operation was higher than LA by 19 h (95% CI [15.77, 22.68], P < 0.00001). Therefore, LA was associated with a significantly lesser duration of hospital stay than GA, which agrees with previous studies [ 12 , 16 , 33 , 37 ]. This is a potential advantage of utilizing LA in the surgical management of CSDH.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we noticed that GA length of operation was higher than LA by 19 h (95% CI [15.77, 22.68], P < 0.00001). Therefore, LA was associated with a significantly lesser duration of hospital stay than GA, which agrees with previous studies [ 12 , 16 , 33 , 37 ]. This is a potential advantage of utilizing LA in the surgical management of CSDH.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, a retrospective study by Bartley et al found that irrigating the solution at body temperature results in lower recurrence rates than at room temperature (48). BHC is most commonly performed under general anesthesia, though local anesthesia is a feasible alternative, with one recent study finding local anesthesia evacuation to result in significantly lower complication rates compared to BHC evacuations performed under general anesthesia (49,50). Similar to twist drill craniostomies, this technique is preferred in the elderly population, where the increased trauma associated with craniotomy has deleterious effects (51-53).…”
Section: Burr Hole Craniostomymentioning
confidence: 99%
“…Being less invasive than a classic craniotomy, the latter two methods are frequently utilized for the initial cSDH evacuation in selected patients 11,12 . Additionally, high-speed drill craniostomy is usually performed with local anesthesia, which is a simpler and safer method promoting better patient recovery 13 and reducing operative time and hospital stay 14 .…”
Section: Introductionmentioning
confidence: 99%